Problematika Kelas Menengah Indonesia: dari Agen Perubahan Menuju Pasivitas Politik - Wahyudin, M Yahya (Interdisciplinary Explorations in Research Journal, 2026)
This study examines the problematic condition of Indonesia's middle class, which has undergone a transformation from an agent of socio-political change into a group that tends toward political passivity. The middle class, which historically played a role as a catalyst for change as evidenced in the 1998 reform movement and the national movement during the colonial era now faces a paradox: possessing substantial social capital, yet trapped in political apathy. This study aims to analyze the structural factors driving the political passivity of Indonesia's middle class within the context of global capitalism and post-reform political dynamics. The method employed is a qualitative approach through literature analysis. Data were drawn from books, scientific journals, research reports, and relevant articles related to the middle class, social change, and political passivity. The primary analytical framework used is Antonio Gramsci's theory of hegemony to dissect the mechanisms by which capitalism dominates middle-class consciousness. The findings reveal that the political passivity of Indonesia's middle class is a product of capitalist hegemony operating through three main channels: (1) a consumer culture that replaces solidarity-based social identity with consumption-based identity; (2) an education system oriented toward producing a capitalist workforce rather than critically engaged citizens; and (3) identity-based political populism that steers the middle class toward pragmatic support for the status quo. This phenomenon is exacerbated by the weakening role of organic intellectuals as a bridge between the middle class and collective consciousness. This study concludes that the revival of the middle class as an agent of change requires critical education, alternative political narratives, and the strengthening of social solidarity as a counter-hegemony against the dominance of global capitalism.